Minocycline promotes dendritic spine maturation and improves behavioural performance in the fragile X mouse model - Bilousova, T V; Dansie, L; Ngo, M; Aye, J; Charles, J R; Ethell, D W; Ethell, I M (Journal of medical genetics, 2009)
Background:Fragile X syndrome (FXS) is the most common single gene inherited form of mental retardation, with behaviours at the extreme of the autistic spectrum. Subjects with FXS and fragile X mental retardation gene knock out (Fmr1 KO) mice, an animal model for FXS, have been shown to exhibit defects in dendritic spine maturation that may underlie cognitive and behavioural abnormalities in FXS. Minocycline is a tetracycline analogue that has been used in clinical trials for stroke, multiple sclerosis and several neurodegenerative conditions.Methods:We evaluated the effects of minocycline on dendritic spine development in the hippocampus of young Fmr1 KO mice, and in primary cultures of hippocampal neurons isolated from those mice. Cognitive effects of minocycline in young WT and Fmr1 KO mice were also evaluated using established behavioural tests for general cognition, activity and anxiety.Results:Our studies demonstrate that minocycline promotes dendritic spine maturation both in cultures and in vivo. The beneficial effects of minocycline on dendritic spine morphology are also accompanied by changes in the behavioural performance of 3-week-old Fmr1 KO mice. Minocycline treated Fmr1 KO mice show less anxiety in the elevated plus maze and more strategic exploratory behaviour in the Y maze as compared to untreated Fmr1 KO mice. Our data suggest that these effects of minocycline may relate to its inhibitory action on MMP-9 expression and activity, which are higher in the hippocampus of Fmr1 KO mice.Conclusion:These findings establish minocycline as a promising therapeutic for the treatment of fragile X mental retardation.